Epidemiology of stroke in Northern Italy: the Cerebrovascular Aosta Registry, 2004–2008 - Corso, Giovanni (Springer Milan, 2012)
Our aim was to prospectively ascertain the incidence of first-ever stroke and ischaemic stroke subtypes, mortality, functional outcome and recurrence in Northern Italy. We identified all possible cases of stroke (1st January 2004 and 31st December 2008). Multiple overlapping sources were used. Standard definitions for incident cases, pathological types and infarction subtypes were used. Patient characteristics were identified and analysed, case-fatality was ascertained from administrative databases, and outcome was assessed in all surviving patients by modified Rankin Scale. We identified 1,326 incident strokes. The pathological diagnosis was confirmed in 94 % of cases. The incidence of first-ever stroke was 80.2 per 100,000 (95 % CI 73–87) when adjusted to world population. The incidence of embolic stroke was significantly greater in women than in men (p < 0.001) whereas the incidence of atherothrombotic stroke was significantly greater in men than in women (p < 0.001). The case-fatality of incident strokes was 9.5 % at 7 day, 16.1 % at 28 day, and 29.9 % at 1 year. Case-fatality of ischaemic stroke was lower than that of other pathological types (p < 0.0001). Hypertension was the most important risk factor, and atrial fibrillation was the most common in embolic stroke. Increasing age, female gender and embolic stroke subtypes were associated with an adverse outcome. Data on stroke incidence and case-fatality were similar to those of other high-income countries. However, differences were found in the distribution of risk factors and prognosis across the stroke types and ischaemic stroke subtypes. Gender differences in long-term functional outcomes were significant.